1995
DOI: 10.1002/j.1556-6676.1995.tb01794.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Supervisor's Race and Level of Support on Perceptions of Supervision

Abstract: The effects of supervision support and supervisor race were examined in a 2 × 2 factorial design (high vs. low

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 21 publications
1
29
0
2
Order By: Relevance
“…6 not found to be related to supervisee ratings of supervision satisfaction or supervision working alliance (Gatmon et al, 2001;Hilton, Russell, & Salmi, 1995). However, Ladany et al (1997) found that supervisory working alliances were stronger when supervisors were equal to or higher (vs. lower) than their supervisees in racial identity development.…”
Section: Journal Of Counselingmentioning
confidence: 92%
“…6 not found to be related to supervisee ratings of supervision satisfaction or supervision working alliance (Gatmon et al, 2001;Hilton, Russell, & Salmi, 1995). However, Ladany et al (1997) found that supervisory working alliances were stronger when supervisors were equal to or higher (vs. lower) than their supervisees in racial identity development.…”
Section: Journal Of Counselingmentioning
confidence: 92%
“…Satisfaction with supervision may indicate several elements within the supervisory environment. For supervisees it may mean a comfortable and supportive supervisory relationship (Hilton, Russell, & Salmi, 1995), communication style of the supervisor, supervisor's supervisory style (Fernando & Hulse-Killacky, 2005), the way in which feedback and suggestions are given, supervisor's genuine interest in the supervisee's development and progress, supervisory behaviors of the supervisor (Hilton et al, 1995), supervisor's sensitivity to the various needs of the supervisee at different stages of the supervisee's development (Stoltenberg, 1981), supervisor's knowledge about clients and their problems, and/or the supervisor's management of the supervisory session time.…”
Section: Discussionmentioning
confidence: 99%
“…Heppner and Roehlke (1984) found that supervisors' behaviors helped increase supervisee selfconfidence, which in turn was positively related to satisfaction with supervision. According to Hilton, Russell, and Salmi (1995), supervisees rated supervision as more satisfying when supervisors created a supportive supervisory environment and demonstrated behaviors that led to establishing rapport, and nurturing and promoting a working alliance. More recently Gatmon and colleagues (2001) explored how the discussion of cultural variables in supervision influenced working alliance and supervisory satisfaction.…”
Section: Introductionmentioning
confidence: 97%
“…Results from these studies report there are racial differences in perceived liking (Cook & Helms, 1988) and in feelings of what constitutes a facilitative relationship (Vander Kolk, 1974). There were no significant race effects for quality of multicultural discussion (Gatmon et al, 2001) and perceived level of support (Hilton et al, 1995). Empirical data also suggest that cultural matching is not necessary for supervision satisfaction or an effective relationship.…”
mentioning
confidence: 86%
“…A review of the literature on cross-racial supervision revealed that most of the literature is more conceptual than empirical. Empirical studies (e.g., Cook & Helms, 1988;Gatmon et al, 2001;Hilton et al, 1995;Ladany, Brittan-Powell, & Pannu, 1997a;Ladany, Inman, Constantine, & Hofheinz, 1997b;Vander Kolk, 1974) tend to examine personality variables as they relate to supervision satisfaction and the working alliance. Results from these studies report there are racial differences in perceived liking (Cook & Helms, 1988) and in feelings of what constitutes a facilitative relationship (Vander Kolk, 1974).…”
mentioning
confidence: 98%